Wall conditioning throughout the first carbon divertor campaign on Wendelstein 7-X. (December 2018) - Wauters, Tom; Goriaev, Andrei; Alonso, Arturo; Baldzuhn, Juergen; Brakel, Rudolf; Brezinsek, Sebastijan; Dinklage, Andreas; Grote, Heinz; Fellinger, Joris; Ford, Oliver P.; König, Ralf; Laqua, Heinrich; et al.
Highlights: Wall conditioning proved to be essential in the first divertor campaign on Wendelstein, 7-X. Baking of plasma vessel and glow discharge conditioning (GDC) in H2 is, performed after the initial pump down of the vacuum vessel to remove water and, carbon oxides respectively. He discharges are successfully applied to establish subsequent plasma density control, in hydrogen plasmas, though He-GDC remained needed to fully offset the hydrogen, inventory build-up. Experienced plasma performance degradation throughout an operational day results, from increased impurity contamination rather than hydrogen saturation of the wall. Abstract: Controlling the recycling of hydrogen and the release of impurities from the plasma facing components proved to be essential and challenging throughout the first divertor campaign on W7-X. This paper discusses the conditioning requirements throughout the first divertor campaign on Wendelstein 7-X. Baking at 150  °C and glow discharge conditioning (GDC) in H2 is performed after the initial pump down of the vacuum vessel. Experimental programs in hydrogen are interlaced with He discharges to desaturate the wall from hydrogen, recover good recycling conditions and hence establish plasma density control. Optimized He ECRH wall conditioning procedures consisted of sequences of short discharges with fixed duty cycle. He-GDC remained however needed before each experimental day to fully offset the hydrogen inventory build-up. A significant increase in the divertor temperature is observed throughout an operational day, enhancing outgassing of CO and H2 O. Preliminary recombination-diffusion modelling of hydrogen outgassing suggests enhanced diffusion to deeper surface layers with increasing wall temperature, which results in better wall pumping. This indicates that the experienced plasma performance degradation throughout an operational day results from increased impurity outgassing at higher wall temperature rather than hydrogen saturation of the wall.